Adventures In Raspberry Pi - Philbin, Carrie Anne (John Wiley & Sons, Inc., 2017)
Build cool Raspberry Pi projects with no experience required! Adventures in Raspberry Pi, 3rd Edition is the fun guide to learning programming. Starting from the very basics and building skill upon skill, you'll learn developing fundamentals even if you've never programmed before